Kajian Awal Keberadaan Hama Gudang Pada Unit Pengelolaan Gabah Beras (Studi Kasus Gudang Gabah Beras UD.BZK dan UD. Pirwan Di Kabupaten Pinrang) - Nur Ilmi; Muh Iqbal Putra; Marwati -; Hikmahwati - (Jurnal Agrotan, 2023)
AWarehouse pests are grouped into three major groups, namely insects, rats, and fungi/mold. The three warehouse pest groups are not always found together in a food commodity storage area. Unlike rats and fungi/mold, warehouse pests are almost always present in food commodity storage areas. With a very small body, flying activity, and resistance to dry conditions, warehouse insects can easily control the environment where warehouse pests live (Kato, 2013). This study aims to determine the types of warehouse pests and their populations in two rice grain management units in Pinrang Regency, carried out at UD BZK and UD Pirwan rice grain warehouses in Pinrang Regency, from December 2021 to January 2022. The study used manual trap methods and bait traps. The results showed that in the rice paddy warehouse of UD BZK there were two insect pests identified, namely Sitophilus oryzae (population of 207.5%) and Tribolium castaneum (population of 40.87%). Meanwhile, at UD Pirwan's grain warehouse, 4 types of insect pests were identified, namely Sitophilus oryzae (population of 31.12%), Tribolium castaneum (total population of 53.87%), Alphitobius diaperinus (total population of 1.62%) and Tenebroides mauritanicus (total population of 1.62%) the total population is 0.5%). The conclusion obtained from this study was that the samples identified from the two rice grain warehouses were found to contain several types of warehouse pests with different populations.